Advanced hemodynamics for prognostication in heart failure: the pursuit of the patient-specific tipping point - Grinstein, Jonathan (Frontiers in Cardiovascular Medicine, 2024)
Background: Objective tools to define the optimal time for referral for advanced therapies and to help guide escalation and de-escalation of support can improve management decisions and outcomes for patients with advanced heart failure. Methods: Here, a physiological framework to define the patient-specific tipping point of myocardial energetics is defined. A novel hemodynamic parameter known as the myocardial performance score (MPS), a marker of power and efficiency, is introduced which allows for the objective assessment of the physiologic tipping point. The performance of the MPS and other advanced hemodynamic parameters including aortic pulsatility index (API) and cardiac power output (CPO) to predict overall myocardial performance was evaluated using a validated computer simulation model (HARVI) as well as a proof-of-concept clinical validation using a cohort of SCAI Stage C cardiogenic shock patients. Results: 1010 discrete heart failure scenarios were modeled. API strongly correlated with the left ventricular coupling ratio (R2 = 0.81) and the strength of association became even stronger under loaded conditions where pulmonary capillary wedge pressure was > 20 mmHg (R2 = 0.94). Under loaded conditions, there is a strong logarithmic relationship between MPS and mechanical efficiency (R2 = 0.93) with a precipitous rise in potential energy and drop in mechanical efficiency with an MPS < 0.5. An MPS < 0.5 was able to predict a CPO < 0.6W and coupling ratio of < 0.7 with sensitivity 87%, specificity 91%. In a cohort of 224 patients with SCAI stage C shock, A baseline MPS score of < 0.5 was associated with a 35% event rate of the composite endpoint of death, LVAD or transplant at 30 days compared to 3% for those with an MPS > 1 (p < 0.001). Patients who were able to augment their MPS to > 1 after milrinone infusion had a lower event rate than those with insufficient reserve (40% vs 16%, p = 0.01). Conclusions: The MPS, which defines the patient-specific power to efficiency ratio, represents an objective assessment of the myocardial energetic state of a patient and can be used to define the physiologic tipping point for patients with advanced heart failure.